Targeting of ΔNp63α by miR‐522 promotes the migration of breast epithelial cells. Issue 2 (10th January 2021) - Dong, Yuanyuan; Long, Juan; Luo, Xingyong; Xie, Gang; Xiao, Zhi‐Xiong Jim; Tong, Ying
Abstract : The TP63 gene, which encodes the p63 protein, is involved in multiple biological processes, including embryonic development and tumorigenesis. ΔNp63α, the predominant isoform of p63 in epithelial cells, acts as an oncogene in early‐stage tumors, but paradoxically acts as a potent antimetastatic factor in advanced cancers. Here, we report that ΔNp63α is a direct target of hsa‐miR‐522 (miR‐522). Induced expression of miR‐522 reduced the levels of ΔNp63α, predisposing breast epithelial cells to a loss of epithelial and acquisition of mesenchymal morphology, resulting in accelerated collective and single‐cell migration. Restoration of ΔNp63α repressed miR‐522‐induced migration. Interestingly, overexpression of miR‐522 did not affect breast epithelial cell proliferation, suggesting that miR‐522 acts specifically through ΔNp63α in this context. Furthermore, expression of miR‐522‐3p and p63 was negatively correlated in human cancer samples. Thus, miR‐522 might be a causative factor for breast tumorigenesis and cancer metastasis. In summary, our results reveal a novel miR‐522/p63 axis in cell migration and thus suggest a potential strategy for therapeutic treatment of cancer metastasis. Abstract : p63 is a p53 family member with pivotal roles in tumorigenesis. Here, we report that hsa‐miR‐522 (miR‐522) is a direct regulator of p63. miR‐522 could promote scattering and migration of mammary epithelial cells through repressing ΔNp63α. The expression of miR‐522‐3p and p63 was negatively correlated in human cancers. The miR‐522/p63 axis might be a potential therapeutic target for cancer metastasis.